AR Implementation as a Media for Recognizing Animal Fossils at Rahmat Gallery Using Markerless Technology - Dwi Lestari, Yuyun; Rizki Maulana, Agung; Setiani Asih, Munjiat (Journal of Computer Science and Informatics Engineering, 2023)
Augmented reality is a technology that combines two-dimensional or three-dimensional virtual differences into a real environment and then projects these virtual objects realistically in real time. The purpose of designing this application is to make it easier for the public or students to find references to scientific works that have been completed by predecessor researchers in an android mobile application. The application design process is carried out using the SketchUp and Unity 3D applications. The results of this study are in the form of an Android-based Augmented reality (AR) application design that can be accessed by the entire community and students very easily. With the design of this application, it is expected to make it easier to find the desired information on the Grace gallry. In designing this application using the SketchUp application in 3D design and designing the Android application using Unity 3D which allows users to display the main page. This application is designed using a system that can make it easier for users to access the application.